Invasive mucormycosis in chronic granulomatous disease - Al-Otaibi, Abdulnasir M. (Saudi Med J, 2016)
Mucormycosis is a rare opportunistic fungal infection that occurs in certain immunocompromised patients. We present 2 cases of invasive mucormycosis due to Rhizopus spp. in patients with chronic granulomatous disease (CGD) and discuss their clinical presentation, management challenges, and outcomes.